2015
DOI: 10.4244/eijv11sva14
|View full text |Cite
|
Sign up to set email alerts
|

OCT for bifurcation stenting: what have we learned?

Abstract: Treatment of bifurcation lesions by percutaneous coronary intervention (PCI) shows major variation in complexity. Intravascular optical coherence tomography (OCT) provides high-resolution images of the pathoanatomy, thrombus, wires and stent positions during the procedure. This information may prove crucial in optimising PCI results and clinical outcomes after complex bifurcation treatment. Mounting evidence confirms the feasibility of OCT in bifurcations, and specific steps where OCT may be advantageous in gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
(49 reference statements)
1
6
0
1
Order By: Relevance
“…Otherwise, we highly suggest that a systematic two‐stent strategy is preferable if a bifurcation lesion has a vulnerable plaque in the MV, particularly localizing at the POC area. Taken together, our results addressed the importance of routine assessment by OCT for bifurcation lesions before decision‐making 9,13,14,17‐19 …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Otherwise, we highly suggest that a systematic two‐stent strategy is preferable if a bifurcation lesion has a vulnerable plaque in the MV, particularly localizing at the POC area. Taken together, our results addressed the importance of routine assessment by OCT for bifurcation lesions before decision‐making 9,13,14,17‐19 …”
Section: Discussionsupporting
confidence: 57%
“…We found that vessels with vulnerable plaques had a wider distal bifurcation angle when measured by OCT but not by QCA. The presence of a wide bifurcation angle leads to a significant chance of restenosis after stent implantation and a disturbed flow pattern caused by the change in wall pressure between the main and bifurcated regions, with the presence of lower wall stress at bifurcations with a wider angle 7,16,17 . Therefore, a link between anatomical abnormality, presence of unstable plaque, and dynamic measurements would be important to guide bifurcation treatment 18‐20 …”
Section: Discussionmentioning
confidence: 99%
“…[2] OCT can provide unique insights in this setting enabling detailed evaluation of coronary bifurcation pathology and facilitating procedural planning. [3] This is the first case in which we implemented OCT imaging to examine coronary artery pathology and use the DEFINITION classification to guide treatment of a bifurcation lesion. OCT imaging did not only permit detection of significant disease and thrombus at the ostium of the diagonal that was not seen by coronary angiography but also provided useful anatomical information and detailed assessment of the reference luminal dimensions and of the length of the lesions that facilitated selection of the appropriate balloon and stent size.…”
Section: Discussionmentioning
confidence: 99%
“…Bifurcation stenting, particularly the 2-stent techniques are associated with a high incidence of underexpansion and malapposition. OCT imaging with its stent rendering, apposition and expansion indicator functions facilitates identification of these abnormalities and hence appropriate corrective actions can be taken to avoid future adverse events (56)(57)(58)(59)(60)(61). Whether the use routine use of OCT to guide bifurcation PCI is associated with better outcomes is being tested in ongoing trials (62).…”
Section: Bifurcation Lesionsmentioning
confidence: 99%